Misyar marriage between shari'ah texts, realities and scholars' fatawa' : an analysis - Osmani, Noor Mohammad (International Islamic University Chittagong (IIUC), 2010)
Marriage is a sacred bond in Islam that ties a man and a woman into a lifelong relationship of love, compassion, mutual understanding, respect and security. It is a firm pledge that one makes in the name of Allah for one-another. ‘Misyar marriage’, ‘Convenience marriage’ or ‘Travelers’ marriage’ is a new form of marriage practiced widely in Saudi Arabia, Egypt and other gulf states. The ‘Misyar bride’ sacrifices some of her marital rights, such as expenses, fixed duration, and an abode. The scholars in Islam have different opinions about this form of marriage. Some of them supported it vehemently, as it could reduce the number of ladies without husbands; while yet others strongly oppose it, as it sounds like part-time wives, which has no roots in Islamic heritage. The present study therefore aims to explore the real status of ‘Misyar or convenience marriage’ in the texts from the Qur’an, Prophet’s Sunnah, the practices of his rightly guided Companions and the Fatawa of the traditional and modern scholars. It would analyze them in the light of the current realities and situations prevailing in many countries of the Muslim world. The study would adopt a critical yet objective approach in dealing with the issue. It is believed that the study would help the Muslim men and women to have clear insights on the issue based on the Shari`ah texts, scholars’ Fatawa and present day realities.